The Normative Construction of Hadith on Halal and Its Transformation Halal Product Assurance Regulations in Indonesia - Ach Baiquni; Ah. Shibghatullah Mujaddidi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2025)
This article explores how hadith-based halal norms are transformed into legal-operational standards within Indonesia’s Halal Product Assurance system. Existing scholarship on halal certification has largely focused on legal, economic, industrial, and technical dimensions, while relatively little attention has been devoted to the process through which hadith functions as a source of normative authority that is subsequently institutionalized within the regulatory framework of a modern nation-state. Drawing on a library-based approach, this article analyzes hadiths concerning halal, haram, doubtful matters (Shubhāt), and slaughtering practices, and traces their transformation into Law No. 33 of 2014 on Halal Product Assurance as well as its implementing regulations issued by the Halal Product Assurance Agency (Badan Penyelenggara Jaminan Produk Halal—BPJPH). The analysis demonstrates that hadith serves not merely as a source of religious and ethical guidance but also as the normative foundation for determining halal criteria, prohibiting specific substances, regulating slaughtering procedures, and governing halal products. Through the mechanisms of bayān, takhṣīṣ, and taqyīd, prophetic norms are transformed from religious authority into positive legal standards implemented through certification systems, material supervision, and halal regulatory governance. This article argues that Indonesia’s Halal Product Assurance system represents a process of the positivization of Islamic law and the institutionalization of prophetic normative authority within the framework of the modern state. By highlighting this transformation, the article contributes to contemporary hadith scholarship and the study of Islamic legal governance by demonstrating how prophetic normative teachings are translated into legal instruments and operational regulatory mechanisms in modern Muslim society.